2013
DOI: 10.4103/0974-7753.114709
|View full text |Cite
|
Sign up to set email alerts
|

Finasteride 5 mg/day treatment of patterned hair loss in normo-androgenetic postmenopausal women

Abstract: Background:There is no consensus on the standard treatment options for female pattern androgenetic alopecia (AGA). Efficacy of finasteride in women is controversial. The purpose of this study was to evaluate the clinical efficacy and safety of 5 mg/day oral finasteride in normoandrogenic postmenopausal woman.Materials and Methods:A total of 40 normoandrogenic postmenopausal women with AGA was enrolled in this study. They were treated with oral finasteride 5 mg/day for 18 months. Efficacy was evaluated by patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 13 publications
3
49
0
7
Order By: Relevance
“…Finasteride dosage for treatment of FPHL varied widely (1–5 mg/day). Four studies suggested that high‐dose (5 mg/day) finasteride use in postmenopausal patients with FPHL could effectively improve hair loss in 6–12 months . One of the studies further demonstrated no significant difference between premenopausal and postmenopausal groups in the percentage of improvement in scalp hair appearance and changes in hair thickness .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finasteride dosage for treatment of FPHL varied widely (1–5 mg/day). Four studies suggested that high‐dose (5 mg/day) finasteride use in postmenopausal patients with FPHL could effectively improve hair loss in 6–12 months . One of the studies further demonstrated no significant difference between premenopausal and postmenopausal groups in the percentage of improvement in scalp hair appearance and changes in hair thickness .…”
Section: Resultsmentioning
confidence: 99%
“…Current research on finasteride in premenopausal and postmenopausal women with FPHL has highlighted its use in high (5 mg/day), medium (2.5 mg/day), low (1.25 mg/day), and lower (1 mg/day) doses. This range has predominantly improved hair loss in women with FPHL, but evidence from RCTs suggests otherwise for high and low doses, and high‐powered studies are lacking for medium and low doses in the past 20 years (Table ). Interestingly, the high finasteride doses that did demonstrate improvement were only studied in postmenopausal women, and none were RCTs .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations